Dynamic Logistic Agility as a Mediator: Aligning Digital Transformation, Business Model Innovation, and Logistic Competency for Superior Business Performance - Edward Cesario; Timotius FCW Sutrisno (SAFE-Network, 2026)
The global supply chain environment requires Third-Party Logistics (3PL) providers to adopt digital capabilities in order to maintain their edge over competitors. This study explores the effects of Digital Transformation (DT), Business Model Innovation (BMI), and Logistics Competency (LC) on Business Performance (BP), both directly and indirectly through Digital Logistics Agility (DLA) at PT Laju Prima Logistik. Employing a quantitative methodology with Partial Least Squares Structural Equation Modeling (PLS-SEM) on data gathered from 34 managers and supervisors, the results confirm that the theoretical framework has strong predictive power, with the model accounting for 80. 8% of the changes in BP. The analysis demonstrates that DLA (β =0.577, P=0. 004) and BMI (β=0.553, P=0.012) are the most important direct factors influencing BP. Notably, the research uncovers a critical implementation gap, even though there is a substantial intent (DT coefficient of 0. 504), neither DT nor LC plays a significant role in predicting DLA, indicating that LPL’s strategic goals are not effectively being converted into flexible technological capabilities. This shortcoming is associated with limited uptake of sophisticated systems such as AI/ML (DLA2 average score of 4.85). The failure to systematically generate DLA results in the dismissal of all mediating hypotheses. Strategic advice includes focused investments in advanced digital micro-foundations (AI/ML) and addressing underlying process issues (LC3) to enable sustainable growth.